The efforts of English teachers in implementing their personality competence in ELT - Putri Rahmatul Fadlillah; Huriyah; Listiana Ikawati (Foreign Language Instruction Probe, 2025)
Personality competence is a crucial aspect of teacher professionalism that affects teaching effectiveness, interaction with students, and adaptation to various dynamics of the educational environment. This study aimed to investigate the strategies applied by English teachers in ELT to implement their personality competence, as well as to identify the challenges faced and the solutions employed. Using a qualitative approach with a case study design, this research involved English teachers at a junior high school in West Java as participants. Data were collected through interviews and document analysis, which focused on exploring teachers’ perceptions and experiences related to their personality competence. The findings indicate that English teachers apply various strategies in the classroom including acting according to religious, legal, social, and national cultural norms; being honest and noble figure and serving as a role model; demonstrating stability, maturity, wisdom, and authority; and demonstrating a work ethic, high responsibility, pride in being a teacher, and confidence. The challenges encountered include balancing professional and personal duties; maintaining emotional demands in diverse classrooms; sustaining motivation; and dealing with excessive workload and expanding professional duties. Solutions applied by the teachers include adapting professional expectations to personal circumstances; regulating emotions; restoring motivation through personal and professional renewal; and embracing continuous learning and collaborative problem-solving. The implications emphasize the importance of institutional support in developing teacher personality competence.